1998
DOI: 10.1046/j.1365-2796.1998.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of quinapril and metoprolol on glycaemic control, serum lipids, blood pressure, albuminuria and quality of life in non‐insulin‐dependent diabetes mellitus patients with hypertension

Abstract: Treatment with quinapril for 6 months appears to have advantages over metoprolol in NIDDM patients with hypertension. Although treatment with quinapril or metoprolol over 6 months was concomitant with a rise in the HbA1c, increased fasting blood glucose, decreased oral glucose tolerance and decreased C-peptide and insulin responses to a glucose challenge were observed only in patients treated with metoprolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
5
0
3
Order By: Relevance
“…With only a handful of studies on effects of antihypertensive treatment on HRQOL in the diabetic population, our understanding of the treatment choice is limited. While Ostman and colleagues found no significant differences in the overall well-being and symptom scores with either metoprolol or quinapril,(62) McGill and colleagues demonstrated that carvedilol was superior to metoprolol in terms of the perceived burden of DM-related symptoms. (63) This was attributed to the differences in the pharmacological profiles of the 2 drugs.…”
Section: Health-related Quality Of Life In Hypertension With Dmmentioning
confidence: 97%
“…With only a handful of studies on effects of antihypertensive treatment on HRQOL in the diabetic population, our understanding of the treatment choice is limited. While Ostman and colleagues found no significant differences in the overall well-being and symptom scores with either metoprolol or quinapril,(62) McGill and colleagues demonstrated that carvedilol was superior to metoprolol in terms of the perceived burden of DM-related symptoms. (63) This was attributed to the differences in the pharmacological profiles of the 2 drugs.…”
Section: Health-related Quality Of Life In Hypertension With Dmmentioning
confidence: 97%
“…A recent study by Kaiser et al had shown no significant difference in total body insulin sensitivity during treatment with enalapril and nebivolol [47]. Structural and functional normalization of the alterations in the resistance arteries found in patients with essential hypertension has been demonstrated after long‐term treatment with ACE inhibitors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Ein Anstieg der Lebensqualität konnte in der Mehrzahl der Studien für ACE-Hemmer und nur vereinzelt für Betablocker, Diuretika und Calciumantagonisten gefunden werden [1, 9,10,23,28,29,32,39]. Kontrollierte Studien mit älteren Patienten konnten bislang nur für die Substanzen Captopril, Losartan und Telsartan einen Anstieg der Lebensqualität unter Therapie zeigen [6,9,21].…”
Section: Nicht Medikamentöse Einflussfaktorenunclassified
“…Vor diesem Hintergrund weisen unsere Ergebnisse auf einen mögli-chen Vorteil von Quinapril bei antihypertensiv zu behandelnden geriatrischen Patienten. In einer kontrollierten Studie bei Patienten mit Hypertonie und nicht insulinabhän-gigem Diabetes mellitus war Quinapril ebenfalls einer Vergleichssubstanz (Metoprolol) bezüglich der Lebensqualität überlegen [32]. Mehrere Einschränkungen sind bei der Ergebnisinterpretation zu beachten.…”
Section: Nicht Medikamentöse Einflussfaktorenunclassified
See 1 more Smart Citation